Minimal invasive temporary percutaneous right ventricular circulatory support after left ventricular assist device implantation. (16th July 2021) - Natanov, Ruslan; Ricklefs, Marcel; Madrahimov, Nodir; Fleissner, Felix; Haverich, Axel; Kühn, Christian
Abstract:  : OBJECTIVES: Cardiogenic shock is a life-threatening situation with high mortality rates. Mechanical unloading of the left ventricle may be achieved via left ventricular assist device (LVAD) implantation. Postoperative right ventricular (RV) failure, however, has very limited therapeutic options and is associated with increased postoperative mortality. In this paper, we describe a percutaneous right heart bypass for temporary postoperative RV support. METHODS: We retrospectively examined all patients receiving percutaneous RV mechanical support after LVAD implantation. All patients receiving trans-jugular mechanical right heart bypass during or after LVAD implantation in our tertiary medical centre between November 2014 and December 2019 were examined retrospectively. The venous draining cannula was placed in the femoral vein; the pulmonary cannula was placed in the pulmonary artery using fluoroscopy. RESULTS: In total, 14 patients received RV support using the trans-jugular technique. Mean age was 48.4 ± 14.9 years. Nine patients were treated with mechanical circulatory support before LVAD implantation. Biventricular support was done in 7 patients. All patients were treated with an Heartware HVAD . Mean postoperative intensive care unit stay was 46.3 ± 32.4 days. Mean right heart bypass support time was 10.6 ± 4.3 days. Twelve patients (86%) could be bridged to RV recovery, RV assist device implantation or heart transplantation. CONCLUSIONS: Percutaneous RV mechanical support is feasible, safe and shows acceptable outcome. Early implantation of RV support may contribute to successful outcome after LVAD implantation. Abstract : Despite improved therapeutic options, in-hospital mortality of patients with cardiogenic shock remains very high [1–3].